Panorama do licenciamento ambiental de campos de petróleo do RN - Jeronimo, Carlos Enrique de Medeiros; Limeira, Eliane Patrícia de Souza Ferreira; Medeiros, Mariana Lopes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The state of Rio Grande do Norte is the third producer of oil and natural gas that is its main mineral extraction activity. According to data from PETROBRAS (2007), there are reserves of about 410 million barrels of oil and 133 million natural gas in Potiguar. Thus, oil activities are vital to the economy of Rio Grande do Norte, and receipt of royalties, one of the main sources of income of the state and its municipalities. Environmental Licensing is the administrative procedure by which to evaluate the location and permitted the establishment and operation of enterprises considered effectively or potentially causing pollution or environmental degradation, and the IDEMA as Decree. 14.338, of 25/02/1999, which approved the Regulation of this organ, responsible for formulating, coordinating, implementing and overseeing the state policy of preservation, conservation, utilization, rational use and protection of environmental resources (Art. 2 , III ). More specifically, Article 14 says that it is for the Coordination of Environment (CMA) of IDEMA analyzes projects and other documents relating to the grant or renewal of license and deployment of equipment and pollution control systems. The present study aims to conduct a quantitative survey in Environmental License for the oil activity in the State of Rio Grande do Norte. The study was conducted at the Institute of Sustainable Development and Environment (IDEMA), linked to the Department of Planning and Finance (SEPLAN) authority. The work consisted of the survey collected information on existing processes in the state EPA, through the electronic system of environmental licensing IDEMA called "CERBERUS”.